Bicyclobutanes: from curiosities to versatile reagents and covalent warheads. Issue 40 (1st September 2022) - Kelly, Christopher B.; Milligan, John A.; Tilley, Leon J.; Sodano, Taylor M.
Abstract : A flurry of reports for preparing, functionalizing, and using bicyclo[1.1.0]butanes (BCBs) have positioned them to be powerful synthons with numerous applications. This review discusses the recent developments regarding this strained carbocycle. Abstract : The unique chemistry of small, strained carbocyclic systems has long captivated organic chemists from a theoretical and fundamental standpoint. A resurgence of interest in strained carbocyclic species has been prompted by their potential as bioisosteres, high fraction of sp 3 carbons, and limited appearance in the patent literature. Among strained ring systems, bicyclo[1.1.0]butane (BCB) stands apart as the smallest bicyclic carbocycle and is amongst the most strained carbocycles known. Despite the fact that BCBs have been synthesized and studied for well over 50 years, they have long been regarded as laboratory curiosities. However, new approaches for preparing, functionalizing, and using BCBs in "strain-release" transformations have positioned BCBs to be powerful synthetic workhorses. Further, the olefinic character of the bridgehead bond enables BCBs to be elaborated into various other ring systems and function as covalent warheads for bioconjugation. This review will discuss the recent developments in the synthesis and functionalization of BCBs as well as the applications of these strained rings in synthesis and drug discovery. An overview of the properties and the historical context of this interesting structure will be provided.